THE TEACHER'S ROLE IN MOTIVATING STUDENTS IN PHYSICS LEARNING USING THE LEARNING MODEL BACKWARD BY DESIGN - Dethan, Jennicha Christiani; Martha, Kurniawati (Universitas Tanjungpura, 2023)
Learning motivation is an action that drives a person to do a learning activity and achieve the purpose of learning. Without the motivation to learn, learning becomes meaningless. The problem found was there is a lack of student motivation to learn Physics. A solution that can be used to grow a student's learning motivation is the application of a design model. The method used was a qualitative descriptive method at one of the high schools in East Lampung. The purpose of this writing is to describe the role of a physics teacher in motivating students to learn physics by using the Backward by Design model. The result of the research shows that the Backward by Design model can be used by the teacher to motivate students in learning Physics.